Post-Koiné: Studies of Non-Anthropocentric (Poetic) Languages - Jarzyna, Anita (Human-Animal Studies, 2025)
In this book you will come across an authorial formula of extrahuman community and communication. The formula includes languages polemical with the narrow model of community that often excludes certain human and non-human beings. Alternative languages are sensitive to the codes of violence directed against animals so as to inclusively create a new interspecies non-antagonistic collectivity. What especially seeks such alternative languages is poetry. It not only represents the true character of existing relationships with animals or determines their shape but also can interfere in them, suspend the control of logocentric order, and, as a result, reduce the ambiguous human guardianship over animals that, in turn, requires the verification and questioning of the guardianship's position in language. This publication treats Polish poetry as a statement equal with-if not precursory for-the discursive calls for the abolition of anthropocentric dominance. The book proves that critical reflection on the language that consolidates the community redefines our attitude toward animals.